PATRIOTIC DUTY OR RESENTED IMPOSITION? PUBLIC REACTIONS TO MILITARY CONSCRIPTION IN WHITE SOUTH AFRICA, 1952-1972 - Callister, Graeme (Scientia Militaria - South African Journal of Military Studies, 2011)
It is widely known that from the introduction of the Defence Amendment Act of 1967 (Act no. 85 of 1967) until the fall of apartheid in 1994, South Africa had a system of universal national service for white males, and that the men conscripted into the South African Defence Force (SADF) under this system were engaged in conflicts in Namibia, Angola, and later in the townships of South Africa itself. What is widely ignored however, both in academia and in wider society, is that the South African military relied on conscripts, selected through a ballot system, to fill its ranks for some fifteen years before the introduction of universal service. This article intends to redress this scholastic imbalance.